Mastering Clojure macros write cleaner, faster, smarter code - Jones, Colin (Pragmatic Bookshelf, 2014)
Level up your skills by taking advantage of Clojure's powerful macro system. Macros make hard things possible and normal things easy. They can be tricky to use, and this book will help you deftly navigate the terrain.